The Effects of Salt-Lake Salt Solution on the Strength of Expansive Soil. (19th April 2022) - Zhang, Shaowei; Li, Dongdong
Abstract : Expansive soils are widely distributed and often cause serious damage to structures. Hanzhong expansive soil and Yulin salt-lake solution were adopted to investigate the effect of salt-lake salt solution on the strength of expansive soil. Expansive soils modified with salt-lake salt solutions with different concentrations (0.1, 0.5, and 1.0 mol/L) were evaluated by X-ray diffraction (XRD), Atterberg limit, free swelling, no load swelling ratio, and triaxial compression tests. The improved expansive soil research using salt-lake salt solution was carried out based on the macroscopic mechanical characteristics. Test results showed that the addition of salt-lake solution effectively inhibited the expansibility of soil. With the increase of the concentration of salt-lake solution, liquid limit, plastic limit, plastic index, free expansion rate, no load swelling, cohesion, and internal friction angle of expansive soil were decreased in varying degrees, and stress-strain relationship curve gradually showed strain softening trend. The reason for the above results was believed to be that salt-lake salt solution reduced the force between particles on shear surface and reduced mutual hindrance.